Monumentality and the Roman Empire 2007
DOI: 10.1093/oso/9780199288632.003.0014
|View full text |Cite
|
Sign up to set email alerts
|

Creating Form: Architects in the Antonine Age

Abstract: At Miletus we saw a distinction between the workmen contracted to construct the arcades and the architect who designed them. Ancient building projects were usually dominated by architects, who directed a large number of subordinate workmen. Whereas the workmen sometimes challenged an instruction, the architect at the top identified more with the project, and his opportunity for social prestige was greater. Since Aristotle, architects were considered to be both ‘wiser’ and ‘more valued’ than manual workers, bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Praef. 4-7;MacDonald (1982), 122-142;Anderson (1997), 3-67;(2014), 127-139;Wilson Jones (2000), 19-25;Taylor (2003), 9-12;Thomas (2007), 70-103. A degree of ambiguity surrounds Africanus' use of ἀρχιτεκτονέω in the passage and some have suggested that he merely assembled the collection rather than undertook any building work: Harnack (1921), 145;Granger (1933), 157.…”
Section: The Location Of the Librarymentioning
confidence: 99%
“…Praef. 4-7;MacDonald (1982), 122-142;Anderson (1997), 3-67;(2014), 127-139;Wilson Jones (2000), 19-25;Taylor (2003), 9-12;Thomas (2007), 70-103. A degree of ambiguity surrounds Africanus' use of ἀρχιτεκτονέω in the passage and some have suggested that he merely assembled the collection rather than undertook any building work: Harnack (1921), 145;Granger (1933), 157.…”
Section: The Location Of the Librarymentioning
confidence: 99%
“… 2 DeLaine 2002. The Antonine Wall, a less ambitious project, was seen by Thomas (2007, 43) in his study of architecture throughout the empire in the Antonine age as ‘the first great provincial work’ in the reign of Antoninus Pius.…”
mentioning
confidence: 99%
“… 189 For the potential of the arched lintel to become transformed into such a frame (which had not happened by Hadrian's reign), see Thomas 2007: 40–6, 61–5. …”
mentioning
confidence: 99%